KONSEP RIBA DALAM AL-QUR’AN - Abdul Ghofur (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
Riba is an economic activity that is prohibited by the Qur’an. Chronologically, the ban has been outlined clearly. On the other hand, bank interest that become one pillar of the existence of financial institutions is rated synonymous with usury. Financial institutions have become a pillar of economic growth. The problem is why the Qur’an forbids usury, whereas various economic activities ‘need’ the existence of interest that are identical to the usury. This study found two findings. First, the prohibition of riba in the Qur’an have preceded other forms of restrictions are more morally intolerable that broadly impacts a major disadvantage in the community. On the other side of the Qur’an strongly encourages the public Makkah to help the poor and orphans around him. Second, the prohibition of riba in the Qur’an has relevance to the real sector of the economy. Therefore, the economy based on usury will naturally ignore the underlying transaction which is the basis of the real sector. As a result of the investors (capitalists) certainly fortunate while the money manager/entrepreneur is still no clarity, so that the position is unbalanced, unjust. The usurious economic system can lead to gaps world community economic growth constantly.